Distinguishing unfolding and functional conformational transitions of calmodulin using ultraviolet resonance Raman spectroscopy. (14th June 2014) - Jones, Eric M.; Balakrishnan, Gurusamy; Squier, Thomas C.; Spiro, Thomas G.
Abstract: Calmodulin (CaM) is a ubiquitous moderator protein for calcium signaling in all eukaryotic cells. This small calcium‐binding protein exhibits a broad range of structural transitions, including domain opening and folding–unfolding, that allow it to recognize a wide variety of binding partners in vivo . While the static structures of CaM associated with its various binding activities are fairly well‐known, it has been challenging to examine the dynamics of transition between these structures in real‐time, due to a lack of suitable spectroscopic probes of CaM structure. In this article, we examine the potential of ultraviolet resonance Raman (UVRR) spectroscopy for clarifying the nature of structural transitions in CaM. We find that the UVRR spectral change (with 229 nm excitation) due to thermal unfolding of CaM is qualitatively different from that associated with opening of the C‐terminal domain in response to Ca 2+ binding. This spectral difference is entirely due to differences in tertiary contacts at the interdomain tyrosine residue Tyr138, toward which other spectroscopic methods are not sensitive. We conclude that UVRR is ideally suited to identifying the different types of structural transitions in CaM and other proteins with conformation‐sensitive tyrosine residues, opening a path to time‐resolved studies of CaM dynamics using Raman spectroscopy.